Inuit Tattoos in Greenland Today: A Marker of Cultural Identity - Jensen Hansen, Tukummeq (Scandinavian-Canadian Studies / Études scandinaves au Canada, 2022)
For years, Greenland has been under Danish colonial rule, which has left the Indigenous People of Greenland with trauma that still haunts them today. The search for identity that has left many young Inuit angry and confused has been difficult to express. Many young Inuit have chosen to use traditional tattoos to heal and strengthen themselves, to show that they are Inuit, to show that they are Kalaallit (Greenlanders). This phenomenon has been seen in Indigenous communities around the world who have experienced similar colonial violence. This essay focusses mainly on the young Inuit from Nuuk, but also discusses the Inuit from Nunavut.